THU0350 Reduced Thickness and Invasion of the Subchondral Bone Plate by Fibrous Tissue are Hallmarks of Joint Remodeling in Ankylosing Spondylitis. (23rd January 2014) - Bleil, J.; Appel, H.; Maier, R.; Sieper, J.; Syrbe, U.
Abstract : Background: The mechanisms contributing to joint remodeling in ankylosing spondylitis (AS) are poorly defined. Objectives: In order to understand the sequence of events leading to joint space narrowing and intraarticular joint ankylosis in AS we performed a histological study analyzing several histomorphometric and histomorphological features in zygapophyseal joints of AS patients in comparison to autopsy controls and patients with osteoarthritis. Methods: Cartilage thickness, thickness of the subchondral bone and trabecular thickness were measured by histomorphometric analysis in zygapophyseal joints from 11 patients with AS, 9 patients with osteoarthritis (OA) and from 10 autopsy controls (CO). In addition, the proteoglycan content according to safranin O staining, apoptosis rates among chondrocytes according to caspase-3 expression and the number of osteoclasts were determined by histochemistry and immunohistochemistry. Results: Cartilage thickness was significantly reduced in joints of both, AS (p=0.0109) and OA patients (p=0.0009), compared to autopsy controls. In contrast, thickness of the subchondral bone plate was only reduced in joints of AS patients compared to autopsy controls (p=0.0003), but not in OA patients (p=0.3664). The trabecular thickness in joints of AS patients was not different from autopsy controls (p=0.4273). Signs of cartilage damage were found in joints of AS patients, in particular in later stages of joint remodeling, i.e. in joints with completely fused joint spaces. Here proteoglycan loss was significantly enhanced compared to controls (p=0.0433) while chondrocyte apoptosis rates were not different (p=0.2176). In contrast to joints of OA patients, which showed proteoglycan loss and enhanced apoptosis primarily within the superficial cartilage layers, proteoglycan loss was dispersed through the whole cartilage area in joints of AS patients. Invasion of fibrous tissue originating from the subchondral bone marrow was found in AS and OA joints. In AS but not OA joints we observed clustering of osteoclasts at the edges of the fibrous tissue directed towards the joint space. Conclusions: These data suggest that degradation of cartilage and of the subchondral bone plate are hallmarks of joint remodelling in AS. In particular loss of proteoglycans accompanies cartilage degradation in AS joints. The fibrous tissue originating from the bone marrow promotes degradation of the subchondral bone plate. Invasion of this fibrous tissue into the subchondral bone plate seems to be particularly promoted in joints of AS patients by clustering of osteoclasts at the edges of the fibrous tissue directed towards the cartilage or joint space. Disclosure of Interest: None Declared